The Influence of Managerial Ownership, Leverage, and BOPO on Creative Accounting Moderated by Corporate Governance - Daud, Rabiatul Adawia Hi.; Nurkholis; Tojibussabirin, Muhammad (Institut Bisnis dan Informatika Kesatuan, 2025)
Financial reporting is essential for transparent corporate performance, yet pressures in merger and acquisition activities heighten the risk of creative accounting. This study analyzes the influence of managerial ownership, leverage, and BOPO on creative accounting practices, as well as the moderating role of Good Corporate Governance (GCG), in the context of mergers and acquisitions in Indonesia to maintain the integrity of financial statements and stakeholder trust. Using a quantitative approach, a sample of 20 companies from 159 merger & acquisition entities registered with the business competition supervisory commission for the 2019-2023 period. Secondary data from financial and annual reports were obtained from the Indonesian Stock Exchange and company websites. Moderated regression analysis through SPSS was used to test the hypotheses. The results show that managerial ownership has no significant effect, leverage has a significant negative effect, and BOPO has a significant positive effect on creative accounting. GCG does not moderate the relationship between managerial ownership and creative accounting, but strengthens the effect of leverage and weakens the effect of BOPO. These findings emphasize the interaction of these factors in influencing financial reporting integrity, providing empirical insights for the application of agency theory.